QUALIDADE DA ÁGUA EM SUB-BACIAS COM DIFERENTES USOS DO SOLO NA BACIA HIDROGRÁFICA DO RIO SÃO JOÃO - Freitas, Lorena Milock de (2016)
Anthropogenic activities developed in watersheds affects water resources, decreasing its quality and quantity. This work was developed in the São João river watershed, supply source in the city of Carambeí (PR), in order to understand the effects of land use and occupation in water quality. Water samples were collected for nine months, from April to December 2015, in two sub-basins, a predominantly native vegetation (sub-basin 1 - 69.8%) and the other with agricultural predominance (sub-basin 2 - 54.1%). The parameters analyzed were dissolved oxygen (DO), temperature, electrical conductivity (EC), pH, total dissolved solids (TDS), turbidity, apparent color, biochemical oxygen demand (BOD), total nitrogen (total-N), total phosphorus (total-P), total coliform (TC) and fecal (FC). Analysis of variance (ANOVA) confirmed that there are significant differences between the collection points. The sub-basin 2 had the lowest averages for DO (6.2 mg L-1) and pH (6.9) and highest averages for temperature (17.8 ° C), color (68.1), turbidity (26.5 UNT) TDS (56.6 mg L-1), EC (76.1 μS cm-1), total-P (1.7 mg L-1), total-N (2.1 mg L-1), BOD (18.2mg L-1) and FC (1451.0 MPN) and presented values above the set by CONAMA nº 357 for total-P, BOD and FC. The sub-basin 1 had values above the set by CONAMA nº 357 for BOD and total-P and high values total-N (1.1 mg L-1). The Pearson correlation analysis showed that there was influence of accumulated rainfall in the sub-basin 1 for turbidity (- 0.70), TDS (- 0.88) and EC (- 0.74) and in the sub-basin 2 to total-N (0.66) and FC (0.67). The atmospheric temperature showed positive correlations with the water temperature, which influenced the parameters in the two sub-basins directly or indirectly, both in maximum, medium and minimum temperatures. The OD showed an inverse relationship with the atmospheric temperature in the two sub-basins. The pH in point 2 had a negative correlation with the atmospheric temperature, and the turbidity point 1 (- 0.67 min. temp. two days). The color had a negative correlation with atmospheric temperature in the two sub-basins. The EC (0.74 min. temp. two days) and CF (0.74 temp. min. two days) showed a positive correlation with atmospheric temperature to the point 2. In general, it was found that the water quality of the sub-basin 2 is strongly influenced by agriculture, coupled with the lack of riparian vegetation and fertilization with animal manure. The sub-basin 1 showed improved water quality due to a higher percentage of native vegetation. However, the lack of Permanent Preservation Area in the springs and farms located upstream of the basin affect water quality.